(untitled) (Research, Society and Development, 2022)
Rutin (RUT) is a flavonoid found in a wide variety of vegetables. It has multiple therapeutic properties, being especially indicated as a venotonic for the treatment of chronic venous insufficiency (CVI). To obtain medicines composed by RUT or associated with other drugs, it is necessary to initially evaluate the stability of the active pharmaceutical ingredient (API), with the objective guarantee the effectiveness and quality of the products, as well as the safety of consumers. Despite being a presupposition for drug registration, there is a scarcity of data in the literature regarding the stability of the API of RUT and its derived products, so this work aimed to perform a critical analysis of publications that address this issue. In view of the prospection, it was possible to divide the information into three groups: evaluation of the stability resulting from the extractive process in plant derivatives, of release systems developed with the purpose of circumventing intrinsic physicochemical limitations of the molecule and in reactive media and environmental conditions designed to degrade the molecule. The results showed that stability studies are challenging from a technical and analytical point of view, since for conducting forced degradation tests and developing stability indicative methods (SIMs), despite the existence of guides, resolutions, and international compendia with the guidelines for guiding the tests, each molecule has a unique chemical nature. Therefore, it is essential to build a stability profile, to propose the control of processes and the development of formulations that contain adjuvants that allow the formation of more stable products.